I.xii.27 Conference, - Labour Party (Ireland) (2007)
MS 49,494/617: File containing: address by Eamon Gilmore TD, Party Leader, dated 17 Nov 2007; circulars to all units of the organisation concerning Party Conference 2007; final agenda for Party Conference 2007; preliminary agenda for Party Conference 2007; final standing orders committee report for Party Conference 2007; and draft standing orders committee report for Party Conference 2007. (35 pp, 2 soft bound volumes)